Commercial Exploitation of Orcidds in Andaman & Nicobar Islands - Rao, P. S. N.; Srivastava, S. K. (Indian Forester, 1996)
A list of 15 promising orchid species out of about 90 occurring in the islands is given for possible commercial exploitation so that this potential resource is turned into wealth in a long run without disturbing the natural habitats. A few suggestions are also made for curbing bulk collections from nature and for successful cultivation in gardens/orchidaria before they are eventually exploited.